2006
DOI: 10.1248/bpb.29.675
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Vitamin E Administration on Acute Gastric Mucosal Lesion Progression in Rats Treated with Compound 48/80, a Mast Cell Degranulator

Abstract: Compound 48/80 (C48/80) is known to cause degranulation of connective tissue mast cells, but not mucosal mast cells, with release of serotonin and histamine from the cells. 1,2) We have shown in rats with a single C48/80 treatment that the development of gastric mucosal lesions occurs with decreases in Se-glutathione peroxidase (Se-GSHpx) activity and vitamin E and hexosamine levels and increases in neutrophil infiltration, xanthine oxidase (XO) activity, and lipid peroxide level in the gastric mucosal tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…This enriched oral supplement can be a useful adjuvant therapy in patients with ulcerative colitis. Ohta et al (2006) found that the gastric mucosa of C48/80‐treated rats had decreased Se, GPx, and vitamin E activity. They suggested that vitamin E prevents acute gastric mucosal lesion progression in C48/80‐treated rats possibly by suppressing the oxidative stress.…”
Section: Discussionmentioning
confidence: 94%
“…This enriched oral supplement can be a useful adjuvant therapy in patients with ulcerative colitis. Ohta et al (2006) found that the gastric mucosa of C48/80‐treated rats had decreased Se, GPx, and vitamin E activity. They suggested that vitamin E prevents acute gastric mucosal lesion progression in C48/80‐treated rats possibly by suppressing the oxidative stress.…”
Section: Discussionmentioning
confidence: 94%
“…We therefore hypothesized that the antioxidant activity of MMBP is important in the healing of gastric lesions. Ohta et al [38] have reported that vitamin E prevents the degradation of gastric mucosa in compound 48/80-treated rats through its antioxidant activity. We have reported that MMBP inhibits dye exudation in rat skin induced by passive cutaneous anaphylaxis or chemical mediators, histamine, serotonin, and substance P, and inhibits histamine release from mast cells induced by compound 48/80 [2,7].…”
Section: Resultsmentioning
confidence: 99%
“…Although some authors consider Tween 80 to be a suitable vehicle for the preparation of vitamin E solution (Krishnamurthy & Bieri, 1963;Kalender et al, 2004;Ohta et al, 2006) the pro-oxidant effect observed in our previous study demonstrated that this method should be avoided. In future studies, an alternative is the dissolution of vitamin E in another vehicle, such as corn oil (Domitrovic et al, 2008).…”
Section: Correlation Of Cell Proliferation and Oxidative Parametersmentioning
confidence: 74%